The negative correlation between foreign savings and domestic savings - Mapalad, Maria Claret M.; Liverakos, Petros K. (1997)
We show that the negative correlation between foreign and domestic savings arises from the non-stationarity of these variables. We impose a more appropriate technique for testing a causal relation such as the one claimed by the revisionist view.
Keywords: Saving and investment; Income; Economic assistance